Dance improvisations : warm-ups, games and choreographic tasks. - Reeve, Justine, ....- (Champaign : Human Kinetics, 2011)
Dance Improvisations: Warm-Ups, Games and Choreographic Tasks will provide assistance with any doubts that dancers and teachers might have with improvisation. This practical book promotes creativity that can lead to innovative breakthroughs among students from middle school age through college. With Dance Improvisations: Warm-Ups, Games and Choreographic Tasks, you receive expert instruction in planning, teaching, and assessing students' improvisations; * 73 activities in creating movement and material for choreographing dances; * a glossary of dance and choreographic terms; * and extensions of each improv to aid further exploration and development of the improvisation skills. The activities support all portions of your class-including improvisation lessons that you can use as warm-ups, games that stimulate creativity, and choreographic tasks for creating movement material. Each activity has been tested and refined by the author, a veteran dance instructor and choreographer. You
Can use the improvs individually in a lesson or use them in developing entire lesson plans. The step-by-step instruction and teaching tips that you receive save you valuable preparation time-and the instructions are clear enough that more experienced students can use the book to practice on their own. With Dance Improvisations: Warm-Ups, Games and Choreographic Tasks, you will find new ways to help your dancers create original movements through both individual and group activities. Your students will hone their creative responses, and the innovation and energy in your dance classes will fill your studio or classroom. Students will blossom and gain inspiration using these improvisations as they learn how to develop movement and choreograph studies. Lesson plans and resource for dance and physical education teachers from middle school through university level
Inhoudsopgave : Chapter 1. Introduction to Improvisation Chapter 2. Warm-Up Improvisations Chapter 3. Creating Movement Material Chapter
4. Movement Improvisations Chapter 5. Exploring Contact Improvisation Chapter 6. Developing Improvisations
Keywords: Improvisatie -- Dans